Computed Tomography of thyroid gland in dogs - Singh, Narendra; Bishnoi, P.; Palecha, Sakar; Bishnoi, A.K.; Diwedi, Shivangi; Galgat, Komal; Patwa, Ruchi; Kumari, Ankita (Indian Journal of Veterinary Surgery, 2026)
The present study evaluated the computed tomography (CT) characteristics of the thyroid gland in dogs by assessing its appearance and attenuation values in healthy and hypothyroid animals. A total of 12 healthy dogs and 8 dogs diagnosed with hypothyroidism were included. The mean age and body weight were 4.25 yr and 16.10 kg in healthy dogs, and 7.65 yr and 34.13 kg in hypothyroid dogs, respectively. On transverse and multiplanar reconstructed images, the thyroid gland was assessed for its location relative to the trachea, lobar shape, and lowest, highest, and mean attenuation (HU) values. Dogs with hypothyroidism had significantly lower pre-contrast mean attenuation values (64.48±2.49 HU) compared to healthy dogs (79.93±2.32 HU). Similarly, post-contrast attenuation values were significantly reduced in hypothyroid dogs (101.29±4.47 HU) compared to those with normal thyroid function (122.84±4.86 HU). In conclusion, hypothyroidism is associated with a significant decrease in both pre- and post-contrast CT attenuation values of the thyroid gland. The CT features identified in healthy dogs provide reliable criteria for locating and evaluating the thyroid gland in cervical CT imaging.